Development of strategy and tactics of internal environment in marketing management at "SamAntepGilam" LLC - Usmonova Dilfuza Ilkhomovna (Journal of Contemporary Business Law & Technology: Cyber Law, Blockchain, and Legal Innovations, 2024)
This article introduces the procedure for studying the desires of potential consumers,the rules of providing trade services, the rights of consumers to be served in trade processes, communication with the consumer were considered.